Robert Burns Woodward - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Khairu Aidilnishah, Rizan Jalil; Mohd Asyrak, Deraman; Rajan, Jose; Aziah, Mohd Yusoff (Penerbit UMP, 2009)
Robert Burns Woodward was born in Boston on April 1Oth, 1917, the only child of Margaret Burns and Arthur Woodward.